CDIO project on MaViCo heat compress for tackwondo players - Bah, Aaisha Negeh; Abdullah Ahmed Ba Odhah, Ali; Abdulrahman Abdulaziz Al-Awadhi, Khaled; Mohamed Nasser, Muhammad Iman Ikhwan (Penerbit UTHM, 2020)
Taekwondo is a traditional Korean martial arts sport which is currently practiced by many countries around the world. As claimed by the International Olympics Committee (2015), this sport made its debut in 1988 as a demonstration of Olympic sport in Korea and became an official medal sport in Sydney, Australia in the year 2000. The art of taekwondo develops posture, graceful movement, excellent coordination, and attention to detail. As a martial arts sport, taekwondo is characterized by its emphasis on dynamic techniques for taking mobile stances, speed, flexibility, and endurance in order to perform the whole process perfectly. Thus, athletes are required to have control over their shoulders, back, hips, knees, ankles, and feet when practicing this sport.